Impact of Substance Use Disorder on Presentation and Short-Term Course of Schizophrenia. (2nd April 2014) - Chakraborty, Rudraprosad; Chatterjee, Arunima; Chaudhury, Suprakash
Abstract : The aim of the present study was to compare a cohort of schizophrenia patients with substance use disorder (SUD) with a similar cohort of schizophrenia patients without SUD with regard to sociodemographic variables, clinical variables, psychopathology, anxiety symptoms, depressive symptoms, treatment outcome, and side effect profile of drugs. A total of 143 consecutive inpatients with ICD-10 DCR diagnosis of schizophrenia were included after obtaining informed consent. Patients were evaluated by a semistructured data sheet and Maudsley Addiction Profile. They were then rated by Positive and Negative Symptoms Scale, Calgary Depression Scale, Hamilton Anxiety Rating Scale, and Brief Psychiatric Rating Scale at presentation, three weeks, and six weeks. At three weeks and six weeks, they were also evaluated by UKU Side Effect Rating Scale. Substance abuse was detected in 63.6% schizophrenia patients. Nicotine was the commonest substance followed by cannabis and alcohol. Substance users had longer untreated illness and more depressive symptoms at presentation and six-week follow-up. Dual diagnosis patients had difficulty in abstraction at three and six weeks but not at presentation. Schizophrenia patients with SUD had more depressive symptoms. SUD appeared to mask abstraction difficulties at presentation. Schizophrenia patients with SUD should be carefully assessed for presence of depression.